2012
DOI: 10.1016/j.jfe.2011.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Estimated participation in U.S. carbon sequestration programs: A study of NIPF landowners in Massachusetts

Abstract: a b s t r a c tAlthough carbon sequestration programs for non-industrial forestland owners in Massachusetts are being developed, very little is known about the program attributes of importance to different types of landowners or the likelihood that landowners will participate in any given program. This study estimates the probability that Massachusetts landowners will participate in several carbon offset programs using data from a survey of 3000 Massachusetts forestland owners. Results from an ordered logit di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 7 publications
5
44
0
Order By: Relevance
“…The results suggested that contract length, expected payment per acre, and early withdrawal penalties were significant determinants of program participation. Similar results were identified in a related study by Dickinson et al (2012), which estimated participation of Massachusetts private forest owners across three hypothetical carbon sequestration programs. The program attributes examined included the following: contract length (5, 10, or 15 years), financial incentives ($5, $15, or $30 per acre annual revenue), the requirement for a forest management plan to be in place, and the stipulation of a penalty for early withdrawal from the program.…”
Section: Literature Review Forest Owners' Intent To Enroll In Paymentsupporting
confidence: 84%
See 1 more Smart Citation
“…The results suggested that contract length, expected payment per acre, and early withdrawal penalties were significant determinants of program participation. Similar results were identified in a related study by Dickinson et al (2012), which estimated participation of Massachusetts private forest owners across three hypothetical carbon sequestration programs. The program attributes examined included the following: contract length (5, 10, or 15 years), financial incentives ($5, $15, or $30 per acre annual revenue), the requirement for a forest management plan to be in place, and the stipulation of a penalty for early withdrawal from the program.…”
Section: Literature Review Forest Owners' Intent To Enroll In Paymentsupporting
confidence: 84%
“…Despite the anticipated benefits associated with payments for carbon sequestration policies, only a few studies have explicitly examined the willingness of forest owners in urbanizing regions to enroll in voluntary payments for carbon sequestration programs (Fletcher et al 2009, Markowski-Lindsay et al 2011, Dickinson et al 2012. Recent related research has been conducted on forest owners' attitudes toward carbon sequestration programs (Khanal et al 2016).…”
Section: Aim and Objectivesmentioning
confidence: 99%
“…Respondents had 521 strong preferences for programs yielding higher returns, which is logical and consistent with all 522 previous empirical research (Fletcher, Kittredge, and Stevens 2009;Dickinson et al 2012;523 Markowski-Lindsay et al 2011;Rabotyagov and Lin 2013;Knoot, Rickenbach, and Silbernagel 524 2015;Kelly, Germain, and Stehman 2015;Miller, Snyder, and Kilgore 2012;Miller et al 2014). 525…”
Section: Policy Implications 457 Payments For C Sequestration To Allesupporting
confidence: 74%
“…The majority of previous research has also found non-industrial private forest owners tend to be 526 hesitant to make long-term decisions committing them to managing their forestlands in any one 527 particular way (Dickinson et al 2012;Markowski-Lindsay et al 2011;Newell, Pizer, and Raimi 528 2013;Miller, Snyder, and Kilgore 2012;Miller et al 2014). This unfortunately does not bode 529 well for the prospect of establishing a regional payments for carbon sequestration market within 530 the study area.…”
Section: Payments For C Sequestration To Alleviate Development Pressumentioning
confidence: 99%
See 1 more Smart Citation